Analisis Profitabilitas, Leverage, Dan Biaya Operasional Terhadap Pajak Penghasilan Badan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2018–2023 - Yessica Triwana Putri; Fadjar Harimurti (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to examine the analysis of Profitability, Leverage, and Operating Costs on Corporate Income Tax. This study uses samples from food and beverage companies listed on the IDX in 2018 - 2023. The type of data studied uses secondary data and the source of the data studied is obtained from the Indonesia Stock Exchange (IDX) website. The population of this study was 95 companies and the number of research samples was 26 companies using purposive sampling. The research data collection technique used documentation techniques. The data analysis technique used descriptive statistical analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing including t-Test, F-Test and Coefficient of Determination Test. The results of the study indicate that partially Leverage does not have a significant effect on Corporate Income Tax. Profitability and Operating Costs have a significant effect on Corporate Income Tax. Simultaneously, Profitability, Leverage, and Operating Costs have a significant effect on Corporate Income Tax.